Exploring trends in innovation within digital economy research: A scientometric analysis - Lazuardi Imani Hakam; Eeng Ahman; Disman Disman; Hari Mulyadi; Dzikri Firmansyah Hakam (Economies, 2023)
Significant advancements have been made in studying innovation within the digital economy over the past 20 years. Research on innovation and the digital economy is crucial since it changes all facets of human existence, including business models and entrepreneurial trends. Research regarding innovation in the digital economy has experienced growth over time. However, only a small number of research works have investigated their references using the most widely utilized citation mapping approach, scientometric analysis. This scientometric analysis used 822 published innovation and digital economy research papers from 2000 to August 2023 from the Scopus database. Data analysis and visualization were carried out using biblioshiny (bibliometric package) in R and VOSviewer. According to the data, the study on innovation within the digital economy has grown by 22.75% yearly since 2000. This study offers valuable insight for society, academics, academic institutions, researchers, policymakers, and businesses. The findings reveal the pivotal aspects of the research, derived from the most frequently referenced subjects, publications, authors, and keywords to determine current and future trends in innovation in the digital economy.
Keywords: 330; innovation; digital economy; scientometrics; research trends; biblioshiny; VoSviewer